PENGARUH LEVERAGE (DER), PROFITABILITAS (ROA) DAN OPERATING CAPACITY (TATO) TERHADAP FINANCIAL DISTRESS ( STUDY PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2017-2021 - Dela Tia Jusi; Andis Febrian (CV. Adiba Aisha Amira, 2023)
This study aims to determine how much influence Leverage, Profitability and Operating Capacity have on Financial Distress in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period using the Statistical Package for the Social Sciences (SPSS). With quantitative research methods. The data used is secondary data obtained from the website www.idx.co.id for companies listed on the Indonesia Stock Exchange (IDX). The data collection technique uses the documentation method, namely by collecting documents in the form of annual financial reports for the 2017-2021 period. and data analysis techniques using Descriptive Statistical Analysis, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Test, Simultaneous F Test, Partial T Test, Coefficient of Determination Test. Based on the conclusions of the analysis results, it is known that the significant value of leverage is 0.000 <0.05 with tcount -4.862 <ttable 1.992, so the leverage variable has a significant negative effect on financial distress. The significant value on profitability is 0.000 <0.05 with tcount 9,196 > ttable 1,992. so the predictability variable has a significant positive effect on financial distress. The significant value of Operating Capacity is 0.000 <0.05 with tcount 8.422 > ttable 1.992, So operating capacity has a significant positive effect on financial distress.